Stress and reproduction - Gershon, Eran (Henry Stewart Talks, 2021)
The stress response system & the corticosteroids releasing hormone (CRH) family, The effect of stress on female fertility, ovary, and embryo development, CRH in uterus and gynecological pathologies, The different types of CRH and their roles, The role of stress mechanisms in parturition